Relation between Fiber Diet and Appendicitis Incidence in Children at H. Adam Malik Central Hospital Medan North Sumatra-Indonesia - Damanik, Boyke; Fikri, Erjan; Nasution, Iqbal Pahlevi (BALI MEDICAL JOURNAL, 2016)
Background: Appendicitis is the most occurred acute abdominal case found in children.1 In United States of America alone, there were 250,000 cases annually. The ratio between boys and girls are 3:2, with most cases caused by late diagnosis and the morbidity factor. Previous studies found that there’s a relation between eating patterns, fiber diet and food hygiene as risk factors for appendicitis.1, 2 At the time this paper is written, there hasn’t been any study that explains the relation between appendicitis and the diet pattern of children from various places in Indonesia. Another condition that further motivates this study is a common conception that children hate to consume vegetables and fruits, which contain the much-needed fiber. Obstruction of the appendix lumen is the main cause of inflammation in the appendix. Fecalith makes up one third of appendicitis cases, which is consists of fats (coprosterols), inorganic salts (calcium phosphate), and organic residual (fibers).3 Other causes including obstruction process by hypertrophy of mural lymphoid follicle as a response from the inflammation of the appendix lumen.3 Obstruction of appendix lumen can be caused by low fiber diet, which causes fecalith to build up in appendix lumen.4 The mechanism of lumen appendix inflammation can be caused by lymphoid hyperplasia, fecalith buildup, foreign object or parasite.4 Therefore, a study needs to be done to determine the mortality prediction easier, more efficient, and not static, in which it’s harder to measure the therapeutic response. In this case, lactate clearance is hoped to have the capability to determine the mortality rate in patients with severe sepsis. Method: This research is an analytic with cross-sectional design. The subjects were 35 child patients with appendicitis in RSHAM which fulfilled the criteria of severe sepsis diagnosis, and were receiving treatment in the period of January-December 2014. Results: Male children are the majority of the patients (62.9%) with average age of 11.89 ± 4.16. Laparotomy is the most administered treatment (54.3%), and most of the subjects have low-fiber diet (54.3%). 19 of the subjects have perforated appendicitis (54.3%). Conclusion: There’s a significant correlation between low-fiber diet with appendicitis incidence (p=0.0001). From the 19 patients with low-fiber diet, 14 of them (73.7%) have acute appendicitis. Meanwhile only 2 of the patients (12.5%) with high-fiber diet have acute appendicitis.